The royal secret : a novel - Riley, Lucinda (New York : Atria Paperback, 2019)
"In this suspenseful and heart-pounding novel from New York Times bestselling author Lucinda Riley, an ambitious young journalist unravels a dangerous mystery that threatens to devastate the British monarchy. Keeping secrets is a dangerous game. When Sir James Harrison, one the greatest actors of his generation, passes away at the age of ninety-five, he leaves behind not just a heartbroken family but also a secret so shocking, it could rock the English establishment to its core. Joanna Haslam, an up-and-coming reporter, is assigned to cover the legendary actor's funeral, attended by glitzy celebrities of every background. But Joanna stumbles on something dark beneath the glamour: the mention of a letter James Harrison has left behind--the contents of which many have been desperate to keep concealed for over seventy years. As she peels back the veil of lies that has shrouded the secret, she realizes that she's close to uncovering something deadly serious--and the royal family may be implicated. Before long, someone is on her tracks, attempting to prevent her from discovering the truth. And they'll stop at nothing to reach the letter before she does. Full of salacious scandal, shocking twists, and captivating romance, and written in Lucinda Riley's signature "vividly drawn and lushly atmospheric" (RT Book Reviews) prose, The Royal Secret is "a full-throttle escapist adventure" (Lancashire Evening Post)"--
"In this suspenseful and heart-pounding novel from New York Times bestselling author Lucinda Riley, an ambitious young journalist unravels a dangerous mystery that threatens to devastate the British monarchy"--
Published in 2000 in Great Britain as 'Seeing Double.' Updated and revised edition published in 2018 in Great Britain as 'The Love Letter.' First Atria Paperback and First Atria Books Hardcover editions published in 2019 in the U.S. as 'The Royal Secret.'-title page verso.
Keywords: Reporters and reporting -- Fiction; Family secrets -- Fiction; Women journalists -- Fiction; FICTION -- Suspense; FICTION -- Espionage; Great Britain -- Kings and rulers -- Fiction; London (England) -- Fiction; Novels; Spy fiction; Thrillers (Fiction).; Suspense fiction; Spy fiction; Thrillers (Fiction)